Raphanus Sativus Leaves Ethanol Extract’s Effect on Heart Muscle’s Nuclear Factor Kappa B in Diabetic Rats - Hendrawati, Asri; Djunet, Nur Aini (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Type 2 diabetes mellitus is characterized by hyperglycemia. Hyperglycemia increases oxidative stress that damage cells including in heart muscle. Oral hypoglycemic drugs cant reduce the expression of nuclear factor kappa B (NFkB) which plays an important role in inflammation and cell damage. Radish leaves (Raphanus sativus) are known to have compounds that can reduce the expression of NFkB.This study aimed to determine the effect of radish leaves on the expression of NFkB in heart muscle. The study design was an experimental laboratory post-test control group design. The subjects were DM male Wistar rats (Rattus norvegicus), weight 150-300 grams, 3-4 months old. Rats were divided into four groups and took the treatment orally for 28 days. The 1st group got plain water. The 2nd group got glibenclamide 5 mg/kg BW/day. The 3rd and 4th groups got 50% and 100% ethanol extract of radish leaves. After the end of treatment, the heart's tissue was taken for immunohistochemical (IHC) staining to measure the proportion of NFkB. The intervention of ethanol extract of radish leaves 50% and 100% for 28 days reduced the percentage of NFkB in the heart muscle cell of rats than placebo and glibenclamide 5 mg/kg BW ((p=0.000). There was no difference between radish leaf extract concentration of 50% and 100% for 28 days in reducing the expression level of NFkB in the heart muscle cell of rats (p=0.876).This research has not been done before and is important for the treatment of diabetes mellitus in the future.